A Reassessment of the Course of Evolution of Wheat - Kimber, Gordon (1972)
Chromosome pairing in hybrids involving Triticum aestivum and new accessions of T. speltoides, and in an amphiploid of these species, indicates that T. speltoides can no longer be considered to be the donor of the B genome of the polyploid wheats. This necessitates a reconsideration of the genome relationships and evolutionary processes that gave rise to cultivated wheats.